Causes of lethal blunt injuries: Autopsy study - Gurger, Mehtap; Gurger, Murat; Yilmaz, Mustafa; Turkoglu, Abdurrahim; Gul, Evrim (Kuwait Medical Assoc, 2023)
Objective: To investigate the cause of blunt traumatic death and the injury profile that may contribute to the medical interventions Design: Retrospective study Setting: Firat University, School of Medicine, Elazig, Turkey Subject: Patients (n=368) who had died due to blunt trauma for three years and who had undergone autopsy were included in the study. Intervention: None Main outcome measures: Demographic data, injury mechanism, detailed injury profile, medical records, autopsy report, Injury Severity Score (ISS) and Revised Trauma Score (RTS), cause of death and place of death were recorded. Preventable deaths were determined by using World Health Organization criteria. Results: Mean age of the patients was 44.7 +/- 23.3 years and the majority were male (78.8%). Mean ISS was 38.1 +/- 13.9; mean RTS was 3.9 +/- 2.6. The most common cause of death was multiple fatal injuries (40.5%), followed by head trauma (32.1%) and hemorrhage (17.1%). Half of the deaths (49.7%) occurred at the site or within the first one hour and 64.7% of the patients died within the first 24 hours. The total preventable/potentially preventable mortality rate was 12.8%, and the most common cause of these deaths was hemorrhage. Conclusions: In our study, we found that fatal blunt traumas were mostly caused by traffic accidents, and half of the patients died at the scene or within the first hour after trauma. The most common cause of blunt traumatic deaths was multiple fatal injuries, whereas hemorrhage was the leading cause of preventable deaths.
Keywords: injuries; non-penetrating; postmortem examination